Hubungan Kepemimpinan Dengan Kinerja Perawat di Ruang Anggrek dan Gladiola Rumah Sakit Husada Jakarta - Efkelin, Ria; Utami, Ressa Andriyani; Mailintina, Yurita (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: The process or activity of nursing practice used by nurses to provide nursing care to patients is referred to as nurse performance. Therefore, nursing services have become an important component of various health services and play an important role in determining the quality of hospital services. Inadequate leadership is a factor in the low performance of nurses. Objective: This research is to determine the relationship between leadership and nurse performance in the Orchid and Gladiola Treatment Room, Husada Hospital, Jakarta. Methods: This study uses a quantitative descriptive method. Result: There is a significant relationship between leadership and work performance of nurses (p value 0.001 < ? 0.05). with good leadership will affect the work performance of nurses. Conclusion: Good leadership will affect the work performance of nurses in hospitals.